Gramsci's laboratory : philosophy, history and politics - Bianchi, Alvaro (Historical materialism book series, 2020)
The purpose of Gramsci's Laboratory is to interpret the relationship between philosophy and politics in Gramsci's Quaderni del carcere . A milestone in contemporary Brazilian Gramsci reception, the book argues that in Gramsci's work the unity of theory and practice is unfolded theoretically through the unity of philosophy, history and politics. Bianchi argues that this unity was developed in the research project that Gramsci carried out in prison, and was thus a product of the 'determination in the last instance' of politics itself. His book demonstrates that a correct understanding of this unity requires us to recognise that history and philosophy are constitutive elements of the political field from which they claim to keep their distance. This book was first published in Portuguese in 2008 as O Laboratório de Gramsci: Filosofia, História e Política by Alameda, ISBN 9788598325798.